Asian Policy of the Chilean Military Regime (1973-1979): The Communication Strategy Against Isolation, the Case of China [Política Asiática del Régimen Militar Chileno (1973-1979): La Estrategia Comunicacional Contra el Aislamiento, el Caso de China] - Alvarez-Valdes, R (Ariadna Ediciones, 2021)
This paper studies the Communication Strategy of Chile´ Foreign Policy towards China, in the period 1973-1979. With this aims, through the collection of primary data product of work with secret, reserved and ordinary documents, as well as telex and notes of archive, the study from a multidisciplinary approach (International Relations, Present Time and Communication) analyzes the bilateral relations of these countries. It has been concluded that bilateral relations in the 70s was not a continuum, but was subdivided into two stages, which represented a complex scenario to be solved for the Communicational Strategies of Chile s foreign policy; in which China was central so that the Civic-Military Dictatorship would not be completely isolated from the international system. In the same way, it was possible to determine the subjects on which both States exchanged ideas, visions and positions for the categories of Internal Policy of Chile, Bilateral Relations Chile-China and Regional and International Policy of Chile. In this way, the research, thinking about current and future bilateral relations, allows us to look at a historical moment in which the tensions and problems of the Chilean Communicational Strategy towards China had not been visualized; and it is a contribution to understand how this country was relating and establishing its position to determine the way it communicated with Chile. © 2021 Ariadna Ediciones. All rights reserved.